The tourism space of Barlinek in the context of spatial models - Łuć, Bartłomiej (Turyzm/Tourism, 2018)
This article describes the tourism space of Barlinek in the context of a spatial model. On the basis of field studies and analyses of tourism attractions and elements of tourism development, the author has compared and adapted the models developed by S. Liszewski (1995) and B. Włodarczyk (2011). Moreover the author has developed an extended SWOT analysis of Barlinek’s tourism space.